Results of balloon pulmonary valvoplasty in children with Noonan's syndrome. (10th January 2018) - Holzmann, Jonathon; Tibby, Shane M.; Rosenthal, Eric; Qureshi, Shakeel; Morgan, Gareth; Krasemann, Thomas
Abstract: : Pulmonary valve stenosis is common in patients with Noonan's syndrome. The response to balloon valvoplasty varies. We assessed the correlation between re-intervention rate, immediate response, and the progress of the valve gradient over time after intervention. Methods: This is a retrospective study conducted from 1995 to 2014. Results: Of 14 patients identified, seven had re-intervention 28±54 months (range 3–149, median 3.3) after valvoplasty. These patients did not have a significant decrease in gradient after intervention. Their gradient subsequently decreased during follow-up and then became static before increasing years after intervention. In contrast, the gradient of patients not requiring further intervention continually reduced over time. Demographics did not differ between these groups. Conclusion: We could not identify predisposing factors for long-term success of pulmonary valvoplasty in Noonan's patients, but the trajectory of gradients differs significantly between patients needing re-intervention from those who remain free from re-intervention.